Peran Ekonomi Islam dalam Mendukung Pembangunan Berkelanjutan - Anton Anton (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the role of Islamic economics in supporting sustainable development through the application of the principles of justice, balance, and social welfare. Sustainable development focuses not only on economic growth but also encompasses sustainable social and environmental aspects. In this context, Islamic economics offers a development concept oriented towards the welfare of society through instruments such as zakat, waqf, Islamic finance, and Islamic business ethics. This study used a qualitative method with a literature review approach, drawing on sources from scientific journals, books, and official documents related to Islamic economics and sustainable development. The results indicate that Islamic economics makes a significant contribution to supporting sustainable development, particularly in poverty reduction, increasing financial inclusion, empowering MSMEs, and strengthening ethical and environmentally friendly investments. Furthermore, the implementation of Sharia principles in economic activities can create more equitable and long-term economic stability. This study concludes that Islamic economics can be a relevant alternative economic system for realizing sustainable development in Indonesia. Therefore, synergy is needed between the government, Islamic financial institutions, and the community to optimize the application of Islamic economic principles to support the achievement of sustainable development goals.